2009
DOI: 10.1021/ja807622w
|View full text |Cite
|
Sign up to set email alerts
|

Imperfect Crystal and Unusual Semiconductor: Boron, a Frustrated Element

Abstract: All elements, except for helium, appear to solidify into crystalline forms at zero temperature, and it is generally assumed that the introduction of lattice defects results in an increase in internal energy. beta-Rhombohedral boron, a thermodynamically stable form of elemental boron at high temperature, is known to have a large amount of partial occupied sites, seemingly in conflict with our common knowledge. By using lattice Monte Carlo techniques combined with ab initio calculations, we find that the beta-ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
136
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 53 publications
10
136
1
1
Order By: Relevance
“…Effects of such complicated defects have been studied by Widom and Mihalkovič [159]. Further studies followed [160,161]. Now, we have confirmed that the presence of defects is essential for the boron crystal stability.…”
Section: Cause Of Defectssupporting
confidence: 53%
See 1 more Smart Citation
“…Effects of such complicated defects have been studied by Widom and Mihalkovič [159]. Further studies followed [160,161]. Now, we have confirmed that the presence of defects is essential for the boron crystal stability.…”
Section: Cause Of Defectssupporting
confidence: 53%
“…Now, we have confirmed that the presence of defects is essential for the boron crystal stability. Ogitsu et al have set forth an idea that the electronic structure of β-rhombohedral boron can be characterized as a frustrate system [161]. A similar idea was once aroused by Golikova in terms of "amorphous concept" [162,163].…”
Section: Cause Of Defectsmentioning
confidence: 99%
“…for the extraordinary strong correlation is probably the interaction of 3d atoms with the unique system of the antiferromagnetically organized, partially occupied regular boron sites B(16)-B(20), as recently described by Ogitsu et al [54,55] A systematic Raman study on the changes in the intraand inter-icosahedral force constants upon the interstitial accommodation of foreign atoms in β-rhombohedral boron is in progress.…”
Section: Force Constantsmentioning
confidence: 77%
“…Ogitsu et al [54,55]. describe the partial occupancies of the sites B (13) The claimed purity of our samples (Wacker, Munich) is 99.9999% for any contaminant except carbon (typically 60 ppm).…”
Section: β-Rhombohedral Boron Structure Groupmentioning
confidence: 99%
“…In the same spirit, and as a way to validate our methodology, we also investigated the structural properties of the ground state of pure sulfur (α-S). Sulfur is one of the very few elements for which full first-principles relaxation calculations have not been performed (boron being another element known for the difficulties that its crystalline ground state presents 6 ).…”
Section: Introductionmentioning
confidence: 99%